Manīshī kī lokayātrā : Mahāmahopādhyāya Paṃ. Gopīnātha Kavirāja kā jīvana-darśana - Siṃha, Bhagavatī Prasāda (Viśvavidyālaya Prakāśana, 1980)
Biography of Gopi Nath Kaviraj, 1887-1976, Indologist and exponent of tantra.